Assessing new child welfare worker competency through social simulation with standardized clients: rubric development and pilot testing. Issue 5 (19th October 2020) - Havig, Kirsten; Pharris, Angela; McLeod, David Axlyn; Natale, Anthony P.; Miller-Cribbs, Julie
ABSTRACT: Child welfare training programs for new employees strive to develop and implement competency-based training approaches. The authors of this article describe the development and validation of a rubric to measure the readiness of new child welfare workers for client engagement and interviewing. The rubric was designed to measure key competencies, based on a review of the literature, including rapport-building, communication and information gathering; and critical safety assessment. The rubric was designed for use with social simulation training, where participants are observed as they simulate skill demonstration toward mastery of competencies. Analysis of both adult and child rubrics revealed good validity and high inter-rater reliability, highlighting their value for the evaluation of new child welfare worker readiness based on key competencies necessary for effective practice.